تيورى گێشتاڵت لە بنەماكانى بنياد وشيكردنەوەى موزيكدا - محمد، سرود فؤاد; بدن، ناصر هاشم; محمد، دلاوەر مصطفى (جامعة صلاح الدين, 2023)
تم إجراء هذا البحث من منظور نظرية جشطالت الموسيقية. ويشمل البحث حدود وأشكال والبناء الفني في الموسيقى الحديثة. جاءت أشكال الموسيقى من الجهود المستمرة للتجارب وممارسة الموسيقي ذات البرامج المختلفة، وأصبحت فيما بعد طريقة فنية يكون فيها لمبدعي الموسيقى أفكار تناسقية والحان تناغمية ذات أبعاد فلسفية إبداعية، يتم تضمينه في السياق الموسيقي، والذي بالطبع، تتكون من مبادئ محددة تحدد واجبات المؤلف للأشكال والهياكل الموسيقية، ثم تلتزم بالأداء الموسيقي. إن عملية البناء بأي شكل أدبي وفني بشكل عام هي تعبير حضاري وفني عن التجارب الجارية والمستمرة للأداء الفني والفكري العام للعملية الفنية، وبالطبع لا تختلف الأصولية الموسيقية عنها، عن أي فن آخر، بل لها خصوصيتها في الانسجام والتوازن بين الموضوع الذي يستخدمه الفنان، وبين ما هو مطلوب في نظرية الشكل الموسيقي لذلك، فإن هذه الألحان هي نفسها تماما مثل النظريات الموسيقية التي تمنح المؤلف نوعا من الحرية، والتي تتحقق تماما في الشكل والبناء الموسيقي وتؤدي إلى خلق فضاء مطلق للتعبير الموسيقي بشكل حاسم. This research uses Qualitative method in the perspective of music's theory of Gestalt. It also includes borders, research forms, and building in modern music. The Musical forms have come from continuous attempts to experience and apply different musical teas. This has become an artistic method that the composer obtained the ideas of melodies, contrasts and harmonies in the music context. These forms absolutely, have special principles and methods that determine the composers' duty to these forms and musical structures and then abide by musical performance. The process of building in any literal and artistic form in general expresses civilized and artistic experiences of the ongoing experiences of artistic and general intellectual performance of the process. Musical construction is not different from any other art, but rather in the harmony and balance between the subjects that the artist uses. That's why these melodies are exactly the same as musical theories. This gives the composer some kind of freedom. To be absolutely touched in frozen behests and to perform music decisively.
Keywords: نظرية الجشطالت -- البناء الفني -- الإبداع الموسيقي -- الحركة الموسيقية